2018
DOI: 10.1007/s12223-017-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of growth rate and gene expression levels of UPEC by antibiotics at sub-MIC

Abstract: The host is the main environment for bacteria, and they also expose to many antibiotics during the treatment of infectious diseases in host body. In this study, it was aimed to investigate possible changes in growth rate and expression levels of three virulence genes (foc/foc, cnf1, and usp) in a uropathogenic E. coli standard strain within the presence of ciprofloxacin, nitrofurantoin, and trimethoprim-sulfamethoxazole. The UPEC C7 strain was grown on tryptic soy broth-TSB (control), TSB + ciprofloxacin, TSB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Exposure to each antibiotic caused a decreased level of biofilm expression ranging between 0.1-and 0.7-fold changes, while the repression was strong and most significant with amikacin-cefotaxime combination treatment with fold change reaching 0.08, i.e., the consequence of treatment on the average expression profile among all biofilm involving genes constituting the bacterial communities studied. As described in this paper and by others [59][60][61], sub-MICs of combinations have potent effects on attenuating biofilm formation which are totally different from each antibiotic alone.…”
Section: Discussionmentioning
confidence: 65%
“…Exposure to each antibiotic caused a decreased level of biofilm expression ranging between 0.1-and 0.7-fold changes, while the repression was strong and most significant with amikacin-cefotaxime combination treatment with fold change reaching 0.08, i.e., the consequence of treatment on the average expression profile among all biofilm involving genes constituting the bacterial communities studied. As described in this paper and by others [59][60][61], sub-MICs of combinations have potent effects on attenuating biofilm formation which are totally different from each antibiotic alone.…”
Section: Discussionmentioning
confidence: 65%
“…It has been suggested that the sub-lethal doses that most microbial communities are naturally exposed to play a role in cell-to-cell signaling and communication [ 28 ]. In laboratory settings, exposing bacteria to sub-inhibitory concentrations of antibiotics has been demonstrated to have a variety of effects including many that may potentially increase virulence [ 10 , 11 , 29 ]. Our study shows that the effect of sub-inhibitory concentrations of antibiotics on biofilm formation are strain dependent ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sfa operon encodes mannose-resistant adhesions, allowing adhesion to mucosal, endothelial cells, and tissue matrices [ 33 ]. Sub-inhibitory concentrations of both nitrofurantoin and ciprofloxacin have previously been shown to upregulate genes encoding S fimbrial adhesion (sfa) and FiC fimbriae (foc) proteins in UPEC [ 10 ]. Ciprofloxacin has also been shown to increase the hemagglutination titer and surface hydrophobicity of UPEC strains, resulting in a higher expression of surface proteins, which can increase adhesiveness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the effect of a drug can be studied. There are hundreds of research papers evaluating the effect of different antibiotics at different sub-MIC concentrations [26,27]. For instance, the in vivo effects of different sub-inhibitory concentrations of the antibiotic rufloxacin on the adherence properties of E. coli and Staphylococcus aureus were investigated.…”
Section: Discussionmentioning
confidence: 99%